2021
DOI: 10.5267/j.msl.2020.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of entrepreneurial values and entrepreneurial orientation, with environmental dynamism and resource availability as moderating variables, on the financial performance and its impacts on firms’ future intention: Empirical evidences from Indonesian state-owned enterprises

Abstract: This study focuses specifically on the effect of Entrepreneurial Values and Entrepreneurial Orientation on Financial Performance of Indonesian state-owned enterprise and also incorporates Environmental Dynamism (ED) and Resource Availability (RA) as moderating variables which will influence the effect of (i) Entrepreneurial Orientation (EO) on Financial Performance (FP), (ii) Entrepreneurial Values (EV) on Financial Performance (FP), and (iii) Entrepreneurial Values (EV) on Entrepreneurial Orientation (EO). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The link between the composition of ELT and the performance of enterprises seems to be influenced by the features of the industry.Uno, Supratikno, Ugut, Bernarto, Antonio, and Hasbullah [26]have shown interest in investigating the impacts of environmental variables. The industrial organization approach posits that the performance of a corporation may be influenced by the characteristics and dynamics of the industry in which it operates.…”
Section: Connection Between Mediators and Moderators In Theelt-perfor...mentioning
confidence: 99%
“…The link between the composition of ELT and the performance of enterprises seems to be influenced by the features of the industry.Uno, Supratikno, Ugut, Bernarto, Antonio, and Hasbullah [26]have shown interest in investigating the impacts of environmental variables. The industrial organization approach posits that the performance of a corporation may be influenced by the characteristics and dynamics of the industry in which it operates.…”
Section: Connection Between Mediators and Moderators In Theelt-perfor...mentioning
confidence: 99%
“…Poblete 5 concluded that the success of entrepreneurs depended on social responsibility and the entrepreneurial values helped in the process of entrepreneurship. Wang et al, 6 found that individual differences could be identified with personalized education. The comprehensive national power would be measured with innovative and entrepreneurial talents.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, little research has also examined the factors that contribute to success in the industry. The motorcycle taxi sector is counteracted by the fact that they have brought various externalities including insecurity, lack of adherence to traffic rules, an increase in road accidents and fatalities, and negative effects on the health of the riders and the environment which have greatly affected the sustainability of operations in the sector (Uno et al, 2021). This study, therefore, aims to examine the transport sector characteristics and the sustainability of motorcycle taxi businesses.…”
Section: Statement Of the Problemmentioning
confidence: 99%